Presidential Accountability in Wartime President Bush, the Treatment of Detainees, and the Laws of War - Streichler, Stuart (University of Michigan Press, 2023)
The American presidency has long tested the capacity of the system of checks and balances to constrain executive power, especially in times of war. While scholars have examined presidents starting military conflicts without congressional authorization or infringing on civil liberties in the name of national security, Stuart Streichler focuses on the conduct of hostilities. Using the treatment of war-on-terror detainees under President George W. Bush as a case study, he integrates international humanitarian law into a constitutional analysis of the repercussions of presidential war powers for human rights around the world. Putting President Bush's actions in a wider context, Presidential Accountability in Wartime begins with a historical survey of the laws of war, with particular emphasis on the 1949 Geneva Conventions and the Nuremberg Tribunal. Streichler then reconstructs the decision-making process that led to the president's approval of interrogation methods that violated Geneva's mandate to treat wartime captives humanely. While taking note of various accountability options-from within the executive branch to the International Criminal Court-the book illustrates the challenge in holding presidents personally responsible for violating the laws of war through an in-depth analysis of the actions taken by Congress, the Supreme Court, and the public in response. In doing so, this book not only raises questions about whether international humanitarian law can moderate wartime presidential behavior but also about the character of the presidency and the American constitutional system of government.